Susceptibility of Macrosiphum euphorbiae to the parasitoid Aphidius ervi: larval development depends on host aphid genotype. Issue 2 (15th December 2016) - Clarke, Hannah Victoria; Cullen, Daniel; Hubbard, Stephen Francis; Karley, Alison Jane
Abstract: The potato aphid, Macrosiphum euphorbiae Thomas (Hemiptera: Aphididae: Macrosiphini), is a common polyphagous aphid in Europe and North America. However, the factors influencing potato aphid dynamics and susceptibility to natural enemies are largely undescribed, particularly in relation to facultative endosymbiotic bacteria, which can provide protection against parasitism and disease in some aphid species. This study investigated whether potato aphid susceptibility to one of its principal natural enemies, the parasitoid Aphidius ervi Haliday (Hymenoptera: Braconidae: Aphidiinae), varied in relation to aphid genotype and/or endosymbiont presence. Parasitism and aphid fitness assays were conducted on clonal lineages of aphids, harbouring their natural endosymbiont infections, collected over 3 years from separate geographic locations. Parasitized aphids were dissected to quantify parasitoid oviposition, larval development, and mummification. Amongst the 19 clonal lines of M. euphorbiae tested, seven aphid genotypes were identified, and 11 lines harboured one or both of the facultative endosymbionts Hamiltonella defensa Moran et al. and Regiella insecticola Moran et al.; H. defensa infections were associated exclusively with two of the seven M. euphorbiae genotypes. Parasitism resistance was detected in clonal lines belonging to a single aphid genotype and resulted from failure of parasitoid eggs to develop into larvae rather than failure of the parasitoid to oviposit. Contrary with studies of several other aphid species, there was little evidence that H. defensa provided strong protection to M. euphorbiae from parasitism by A. ervi . Furthermore, there were no clear fitness costs to the aphid associated with parasitism resistance or with H. defensa infection. The two M. euphorbiae genotypes in which H. defensa occurred, which included the resistant genotype, exhibited faster development, higher survival, and greater fecundity than the other five aphid genotypes. These findings suggest that biological control of M. euphorbiae using A. ervi alone could exacerbate pest problems by selecting for the fittest parasitism‐resistant genotypes.